Space for the Other Ecumenical Shared Ministries - Beardsall, Sandra; McDonald, William P.; Budde, Mitzi J. (2019)
Ecumenical Shared Ministries (ESM's) combine two or more traditions in a variety of contexts and for as many reasons. The space such congregations share suggests resources for an ESM ecclesiology. Ecumenical parishes live with their multiple traditions in a mutual "otherness" that invites reciprocity, mutual indwelling, and communion. Their shared space"disruptive" of the norms of single-traditioned churchesmarks a shared practice of both acknowledging and dying to boundaries across a history that becomes necessarily experimental. Finally, ESM's witness to the church's cruciform body of self-givingin this case, of one tradition to the otherin a sharing of gifts and graces.
Keywords: Ecumenical Movement; Ecumenical Shared Ministries; Lord's Supper; MANNERS & customs; Mystical Union; Reciprocity (Psychology); communiion ecclesiology; Ecclesiology; ecumenism; U.S. and Canada; Koinonia; LOCAL ECUMENISM; Otherness; Spatiality